Knowledge and Preventive Practice Regarding Dengue Among Community People of Bharatpur-05, Chitwan, Nepal (One Health Journal of Nepal, 2024)
Introduction: Dengue infection transmitted by Aedes aegypti is endemic in Nepal. Gaining a preliminary understanding of people's knowledge and preventive practices will enable health professionals to better comprehend the challenges we face and contribute to the enhancement of dengue prevention programs. The objective of this study was to assess the knowledge and preventive practice regarding dengue among the community people of Bharatpur -5, Chitwan.Methods: A descriptive cross-sectional study was conducted among 188 people of age above 18 through face- to-face interviews using self-developed questionnaires. Data were entered and analyzed into SPSS version 20. The main analytical procedure was descriptive using frequencies, and percentages.Results: The study shows that 21.8% of respondents had adequate knowledge and 11.2% had good preventive practice regarding dengue.Conclusions: Overall, the majority of respondents had been found to have inadequate knowledge and poor preventive practice regarding dengue. This highlights an urgent need for an extensive dengue prevention program.